STRATEGI PEMBELAJARAN FIKIH DENGAN MEDIA POWER POINT BERBASIS ANIMASI - Ainun Khoirotul Ummah, Ainun Khoirotul Ummah; Anas Tania Januari (STAI Ma'had Aly Al-Hikam Malang, 2024)
Learning strategies are patterns of teacher and student interaction to achieve learning objectives. The use of learning media, such as PowerPoint, is effective in conveying information and increasing student motivation, especially in learning fiqh. Jurisprudence focuses on the basic competencies of performing fard prayers which are expected to form disciplined behavior. This research uses a descriptive qualitative approach, with the researcher acting as a data collection instrument through observation, interviews, and documentation. . The learning process of fiqh with power point media strategy runs smoothly although there are some obstacles, fiqh learning strategy with power point media has a very big contribution and can help teachers in the learning process. As well as being able to increase student learning motivation and increase student courage in question and answer. Student motivation can be seen from the increase in student learning outcomes after learning strategies with animation-based power point media. The obstacles found in the learning strategy of fiqh with animation-based power point media are problems related to teacher competence, problems from students, problems from learning media.